2009
DOI: 10.1158/1078-0432.ccr-08-3128
|View full text |Cite
|
Sign up to set email alerts
|

The Breast Cancer Susceptibility Mutation PALB2 1592delT Is Associated with an Aggressive Tumor Phenotype

Abstract: Purpose: To determine the effect of the breast cancer susceptibility mutation PALB2 1592delT on tumor phenotype and patient survival. Experimental Design: We defined the PALB2 mutation status in 947 familial and1,274 sporadic breast cancer patients and 1,079 population controls, and compared tumor characteristics and survival in mutation carriers relative to other familial and sporadic cases and to 79 BRCA1 and 104 BRCA2 mutation carrier cases. Results: The PALB2 1592delT mutation was found in 19 familial [2.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
103
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 46 publications
11
103
1
4
Order By: Relevance
“…An OR of ~11 was estimated in Finnish familial cases and controls in two separate studies for the c.1592delT mutation. 29,30 The French-Canadian c.2323C>T mutation was tested in earlyonset cases and controls, yielding an OR of 103. This OR value was most likely overestimated, given that no mutation carriers were found among controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An OR of ~11 was estimated in Finnish familial cases and controls in two separate studies for the c.1592delT mutation. 29,30 The French-Canadian c.2323C>T mutation was tested in earlyonset cases and controls, yielding an OR of 103. This OR value was most likely overestimated, given that no mutation carriers were found among controls.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 To date, PALB2 recurrent mutations have been reported in four populations. The Finnish c.1592delT (p.Leu531fs) mutation was investigated in two studies 29,30 and identified in 3/113 (2.7%) and 19/947 (2.0%) familial cases and in 6/2,501 (0.2%) and 2/1,079 (0.2%) controls, respectively. The c.2323C>T (p.Gln775X) mutation was detected in 4/564 (0.7%) FrenchCanadian early-onset cases and in 0/6,443 newborn infant controls.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 77 PALB2 mutation-positive cases have been identified mainly in familial or early onset breast cancer cohorts from different populations [13,15,[18][19][20][21][22][23][24][25]. Of the 77 described PALB2 mutation cases, 52 are carrier of the 1592delT Finnish founder mutation, which could influence the currently known phenotype [19,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 77 described PALB2 mutation cases, 52 are carrier of the 1592delT Finnish founder mutation, which could influence the currently known phenotype [19,24,26]. The selection criteria of these previous breast cancer studies varied, but most studies included BRCA1/2 mutation negative early onset breast cancer patients with diagnosis under 50 years or breast cancer patients from families with first or second degree relatives affected with breast-or ovarian cancer in unknown numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent founder mutations in several cancer susceptibility genes, including the BRCA2, PALB2, and RAD51C FA genes, have been identified in the Finnish population (14)(15)(16). The PALB2 and RAD51C founder mutations have been detected at 2% frequency in Finnish breast or ovarian cancer families (15)(16)(17), whereas, in other populations, mutations in these genes are rare and often unique for each family. Founder effects in the isolated populations such as Finland or Iceland may enrich certain mutations and thus explain a significant proportion of all mutations in certain genes (18,19).…”
Section: Significancementioning
confidence: 99%